Prevalenca astme pri odraslih v Sloveniji - Šuškovič, Stanislav (Zdravniški vestnik, 2011)
Background: As prevalence of adult asthma in Slovenia was unknown, a research was performed to disclose this epidemiologic parameter of asthma in Slovenian adults aged 18 to 65 years. Methods: The prevalence of asthma was assessed by combining the results of the recrutation part of the research which took placein seven Slovenian regions where 5908 randomly chosen persons were contacted by phone, and the population part of the research in which 8217 randomly chosen persons from all parts of Slovenia, all aged 18-65 years, werecontacted by phone. Among the latter, 1145 subjects were willing to answerseven questions about their respiratory symptoms. From 5908 subjects primarily contacted in the recrutation part of the research, 185 persons were invited to participate in further questioning and diagnostic procedures ordered by respiratory physicians who examined them. Merging the results of the recrutation and population parts of the research was performed by the CHAID analysis (Chi-squared Automatic Interaction Detector). Results: Among the 185 subjects participating in the recrutation part of the research, there were 37 asthmatics found, 21 of whom previously did not know they had the disease; 20 asthmatics suffered form chronic rhinitis, and only two of them were aware of it. Using the CHAID analysis, we determined that the prevalence of asthma in persons aged 18-65 years in Slovenia is 16 %. Results: Among the 185 subjects participating in the recrutation part of the research, there were37 asthmatics found, 21 of whom previously did not know they had the disease; 20 asthmatics suffered form chronic rhinitis, and only two of them were aware of it. Using the CHAID analysis, we determined that the prevalence of asthma in persons aged 18-65 years in Slovenia is 16 %.
Keywords: asthma; astma; prevalenca; Slovenia; Slovenija